Comprehensive Investigation on Ginsenosides in Different Parts of a Garden-Cultivated Ginseng Root and Rhizome - Junqian Pan; Wei Zheng; Xu Pang; Jie Zhang; Xiaojuan Chen; Ming Yuan; Kate Yu; Baolin Guo; Baiping Ma (Molecules, 2021)
Background: Ginseng is widely used as herb or food. Different parts of ginseng have diverse usages. However, the comprehensive analysis on the ginsenosides in different parts of ginseng root is scarce. Methods: An ultra-high-performance liquid chromatography-quadrupole time-of-flight mass spectrometry (UHPLC-Q-TOF/MS) combined with UNIFI informatics platform and ultra-high-performance liquid chromatography-charged aerosol detection (UHPLC-CAD) were employed to evaluate the different parts of cultivated ginseng root. Results: 105 ginsenosides including 16 new compounds were identified or tentatively characterized. 22 potential chemical markers were identified, 20, 17, and 19 for main root (MR) and fibrous root (FR), main root (MR) and branch root (BR), and main root (MR) and rhizome (RH), respectively. The relative contents of Re, Rb1, 20(R)-Rh1, Rd, and Rf were highest in FR. The relative content of Rg1 was highest in RH. The total relative content of pharmacopoeia indicators Rg1, Re, and Rb1 was highest in FR. Conclusion: The differences among these parts were the compositions and relative contents of ginsenosides. Under our research conditions, the peak area ratio of Rg1 and Re could distinguish the MR and FR samples. Fibrous roots showed rich ingredients and high ginsenosides contents which should be further utilized.